2006
DOI: 10.1080/10408390500511862
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity as Related to Dietary Fiber: A Review

Abstract: Viscosity is a physicochemical property associated with dietary fibers, particularly soluble dietary fibers. Viscous dietary fibers thicken when mixed with fluids and include polysaccharides such as gums, pectins, psyllium, and beta-glucans. Although insoluble fiber particles may affect viscosity measurement, viscosity is not an issue regards insoluble dietary fibers. Viscous fibers have been credited for beneficial physiological responses in human, animal, and animal-alternative in vitro models. The following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
307
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(322 citation statements)
references
References 89 publications
7
307
1
7
Order By: Relevance
“…Furthermore, the addition of husk increased water absorption because of the hydrogen bonding interaction between the hydroxyl groups of water and those of polysaccharide macromolecules present in the fibre (Dikeman & Fahey 2006). If the water absorption increases dramatically, the batter of extremely high viscosity will be a result, in which air bubbles cannot be sufficiently trapped.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the addition of husk increased water absorption because of the hydrogen bonding interaction between the hydroxyl groups of water and those of polysaccharide macromolecules present in the fibre (Dikeman & Fahey 2006). If the water absorption increases dramatically, the batter of extremely high viscosity will be a result, in which air bubbles cannot be sufficiently trapped.…”
Section: Resultsmentioning
confidence: 99%
“…Czuchajowska et al (1992) reported similar results. An increase in the absorption of water is caused by the interaction between the hydroxyl groups of water and those of polysaccharide macromolecules present in the husk (Dikeman & Fahey 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, choosing a sweet potato with low viscosity as the feedstock may be beneficial for reducing the cost of ethanol production. According to several studies, the viscosity of a plant is mainly related to fiber and pectin (Dikeman and Fahey, 2006;Sreenath et al, 1987). The addition of water may also affect the viscosity of the fermentation mash.…”
Section: Statistical Methods and Calculationsmentioning
confidence: 99%
“…For the reason of complexity, measured values of GI fluid viscosity for humans in the fed and fasted states are very limited [48]. Echo-planar MRI was used in humans to monitor the changes in a viscous meals viscosity by Marciani et al [49] and they found significant reduction in the meals viscosity with time due to dilution by the gastric juice [49].…”
Section: Physiological Parametersmentioning
confidence: 99%
“…Viscosity is also affected by pH in addition to soluble meal content and concentration [4]. Test meals containing dietary fibres are administered that have viscosities ranging from 10 to > 10,000 cP [4,48,49] [4,50,51].…”
Section: Physiological Parametersmentioning
confidence: 99%